Thermoplastic elastomer and method for producing the same, suction cup
Patent Information
- Application Number
- CN202611026495.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-09
AI Technical Summary
但是,使用TPE材料制作得到的吸盘往往无法兼顾良好的粘性和硬度,从而难以维持较长时间的悬挂
[0018]本申请通过将兼具软嵌段与硬嵌段的氢化苯乙烯-丁二烯-苯乙烯嵌段共聚物与运动粘度在本申请范围内的矿物油、以及聚α-甲基苯乙烯、增粘剂按照特定的质量份数进行复合,各组分协同作用,制备得到的热塑性弹性体粘性、成型性良好,且硬度适中,不仅可以较为稳固地粘住被测物体表面,还具有较好的硬度以抗蠕变,从而,制得的吸盘可以兼顾较高的吸附力的同时延长悬挂时间。
Smart Images

Figure CN122878708A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of materials technology, and in particular to thermoplastic elastomers and their preparation methods, and suction cups. Background Technology
[0002] Traditional polyvinyl chloride (PVC) suction cups are widely used due to their low cost and ease of processing, but they are relatively sticky to the touch, mostly for single use, and may release plasticizers if exposed to grease or high temperatures for a long time, making them less environmentally friendly.
[0003] Thermoplastic elastomers (TPEs) offer advantages such as good environmental friendliness, high safety, soft touch, excellent weather resistance, fatigue resistance, and temperature resistance, and they are also recyclable. They can be coated and bonded to other matrix materials, such as polycarbonate (PC), to create suction cups for hanging items. However, suction cups made from TPE materials often fail to balance good adhesion and hardness, making it difficult to maintain suspension for extended periods. Summary of the Invention
[0004] Therefore, it is necessary to provide a thermoplastic elastomer that balances good adhesion and hardness, so that the resulting suction cup can extend the hanging time of the object while maintaining high adhesion force.
[0005] The first aspect of this application provides a thermoplastic elastomer, wherein the raw materials for preparing the thermoplastic elastomer, by weight, comprise the following components: 25 to 40 parts of hydrogenated styrene-butadiene-styrene block copolymer, 25 to 40 parts of mineral oil, 2 to 7 parts of polyα-methylstyrene, and 15 to 35 parts of tackifier; wherein the mineral oil has a kinematic viscosity of 420 mm² / s to 460 mm² / s at 40°C.
[0006] In some embodiments, the hydrogenated styrene-butadiene-styrene block copolymer has a linear structure and a weight-average molecular weight of 90,000 g / mol to 120,000 g / mol.
[0007] In some embodiments, the mineral oil includes one of naphthenic oil or paraffin oil.
[0008] In some embodiments, the softening point of the poly-α-methylstyrene is 130°C to 150°C.
[0009] In some embodiments, the tackifier comprises either C9 petroleum resin or C5 petroleum resin.
[0010] In some embodiments, the raw material further includes an antioxidant, which includes at least one of tris[2,4-di-tert-butylphenyl]phosphite and β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester; the antioxidant is present in parts by weight of 0.1 to 0.5 parts based on the mass of the raw material excluding the antioxidant.
[0011] The second aspect of this application provides a method for preparing a thermoplastic elastomer, comprising the following steps: mixing 25 to 40 parts by weight of a hydrogenated styrene-butadiene-styrene block copolymer with 25 to 40 parts by weight of mineral oil to obtain a premix; mixing the premix with 2 to 7 parts by weight of polyα-methylstyrene and 15 to 35 parts by weight of a tackifier to obtain a mixture; and extruding and granulating the mixture to obtain the thermoplastic elastomer.
[0012] In some embodiments, the preparation method satisfies at least one of the following characteristics:
[0013] (1) After the first mixing, let the premix stand for 48h to 72h;
[0014] (2) The extrusion temperature is 170°C to 190°C;
[0015] (3) The granulation process is water ring granulation, which is carried out in a solution containing an anti-sticking agent, wherein the anti-sticking agent includes at least one of zinc stearate and calcium stearate.
[0016] In some embodiments, the preparation method further includes the following steps: after extruding the mixture, the mixture is further passed through two layers of 300 mesh ± 10 mesh filters and two layers of 80 mesh ± 10 mesh filters in sequence.
[0017] A third aspect of the present invention provides a suction cup comprising a thermoplastic elastomer of any of the above embodiments or a thermoplastic elastomer prepared according to the method of any of the above embodiments.
[0018] This application combines a hydrogenated styrene-butadiene-styrene block copolymer with both soft and hard blocks, mineral oil with a kinematic viscosity within the scope of this application, poly-α-methylstyrene, and a tackifier in specific mass proportions. The synergistic effect of these components results in a thermoplastic elastomer with good adhesion and formability, and moderate hardness. It can not only adhere firmly to the surface of the object being tested, but also has good hardness to resist creep. Thus, the resulting suction cup can achieve both high adsorption force and extended suspension time. Attached Figure Description
[0019] Figure 1This is a photograph of the sample to be tested for peel strength testing in one embodiment of this application.
[0020] Figure 2 This is a schematic diagram of the adhesive strip in one embodiment of this application. Detailed Implementation
[0021] The present application will be further described in detail below with reference to the accompanying drawings, embodiments, and examples. It should be understood that these embodiments and examples are for illustrative purposes only and are not intended to limit the scope of the present application. The purpose of providing these embodiments and examples is to enable a more thorough and comprehensive understanding of the disclosure of the present application. It should also be understood that the present application can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various modifications or alterations without departing from the spirit of the present application, and the equivalent forms obtained also fall within the protection scope of the present application. For example, features described or illustrated as part of one embodiment can be combined in a suitable manner in another embodiment to produce new embodiments. Furthermore, numerous details are set forth in the following description to provide a fuller understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for descriptive purposes only and is not intended to be limiting of the application.
[0023] Unless otherwise stated or in case of contradiction, the terms or phrases used herein shall have the following meanings:
[0024] The terms “and / or,” “or / and,” and “and / or” as used herein include any one of two or more of the related listed items, as well as any and all combinations of the related listed items. “Any and all combinations” includes any two related listed items, any more related listed items, or a combination of all related listed items. For example, “A and / or B” includes three parallel options: A, B, and “a combination of A and B.”
[0025] In this application, the technical features or solutions described in open-ended language include both closed-ended technical features or solutions consisting of the listed contents and open-ended technical features or solutions that include the listed contents.
[0026] In this application, where the method flow involves multiple steps, unless otherwise explicitly stated herein, there is no strict order restriction on the execution of these steps; they can be executed in any order other than those described. Moreover, any step may include multiple sub-steps or multiple stages, which are not necessarily completed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be performed alternately or simultaneously with other steps or parts of the sub-steps or stages of other steps.
[0027] In this application, the terms "first aspect," "second aspect," "third aspect," "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," "fourth," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.
[0028] The hydrogenated styrene-butadiene-styrene block copolymer (SEBS) of this application is composed of styrene-based hard blocks and ethylene-butenyl (EB) soft blocks. The hard blocks act as crosslinking points below the glass transition temperature of polystyrene, while the soft blocks provide elasticity. Therefore, SEBS possesses rubber-like elasticity and exhibits excellent heat resistance and weather resistance. However, SEBS-based thermoplastic elastomers have insufficient adhesion and poor compatibility with PC when coated, making composite with PC materials difficult and resulting in the inability to coat them. Consequently, it is difficult to manufacture suction cups with good adhesion and long hanging time.
[0029] The first aspect of this application provides a thermoplastic elastomer, wherein the raw materials for preparing the thermoplastic elastomer, by weight parts, comprise the following components: 25 to 40 parts of hydrogenated styrene-butadiene-styrene block copolymer, 25 to 40 parts of mineral oil, 2 to 7 parts of polyα-methylstyrene, and 15 to 35 parts of a tackifier; the mineral oil has a kinematic viscosity of 420 mm² / s to 460 mm² / s at 40°C. Specifically, the weight parts of the hydrogenated styrene-butadiene-styrene block copolymer may be, but are not limited to, 25, 26.5, 28, 29.5, 31, 32.5, 34, 35.5, 37, 38.5, or 40. Specifically, the weight parts of the mineral oil may be, but are not limited to, 25, 26.5, 28, 29.5, 31, 32.5, 34, 35.5, 37, 38.5, or 40. Specifically, the mass fraction of polyα-methylstyrene can be, but is not limited to, 2, 3, 4, 5, 6, or 7. Specifically, the mass fraction of the tackifier can be, but is not limited to, 15, 17, 19, 21, 23, 25, 27, 29, 31, 33, or 35. Specifically, the kinematic viscosity of the mineral oil can be, but is not limited to, 420 mm² / s, 422 mm² / s, 424 mm² / s, 426 mm² / s, 428 mm² / s, 430 mm² / s, 432 mm² / s, 434 mm² / s, 436 mm² / s, 438 mm² / s, or 440 mm² / s.
[0030] The specific ratio of mineral oil and tackifier within the aforementioned viscosity range is beneficial for increasing the viscosity of thermoplastic elastomers. When the kinematic viscosity of the mineral oil is too low, such as below 420 mm² / s, the resulting thermoplastic elastomer has a low viscosity, making it difficult to composite with PC, resulting in insufficient suction power in the prepared suction cups. When the kinematic viscosity of the mineral oil is too high, such as above 460 mm² / s, although the thermoplastic elastomer has a higher viscosity, its processing performance is poor, making it difficult to injection mold a suction cup with a good appearance. Similarly, when the content of tackifier or mineral oil is too high, such as above 40 parts, the viscosity of the thermoplastic elastomer is too high, making it difficult to plasticize and produce a suction cup with a good appearance; when the content of tackifier or mineral oil is too low, such as less than 25 parts, the viscosity of the resulting thermoplastic elastomer is too low, making it difficult to composite with PC, resulting in insufficient suction power in the prepared suction cups. Therefore, by compounding the aforementioned mineral oil and tackifier into the thermoplastic elastomer of this application, it is beneficial to increase the viscosity, thereby improving the suction cup's adsorption force. However, as the viscosity of the thermoplastic elastomer increases, its processing performance will slightly decrease. Poly(α-methylstyrene) has good compatibility with the aforementioned mineral oil and SEBS; therefore, the addition of the aforementioned percentages of poly(α-methylstyrene) by mass is beneficial to improving the plasticizing properties of the thermoplastic elastomer, thereby improving the smoothness of the suction cup surface and increasing the adsorption force between the suction cup and the adsorbed surface. Furthermore, the addition of the aforementioned percentages of poly(α-methylstyrene) by mass also helps to moderately increase the hardness of the thermoplastic elastomer, thereby improving the suction cup's creep resistance and suspension performance.
[0031] Therefore, by selecting the above components and compounding them in a specific ratio and adjusting the viscosity of the mineral oil within the scope of this application, the thermoplastic elastomer has good viscosity and hardness while also having good processing performance and plasticizing performance, so that the resulting suction cup can have both high adsorption force and suspension performance.
[0032] In some embodiments, the hydrogenated styrene-butadiene-styrene block copolymer has a linear structure, and its weight-average molecular weight is between 90,000 g / mol and 120,000 g / mol. Specifically, the weight-average molecular weight of the hydrogenated styrene-butadiene-styrene block copolymer can be, but is not limited to, 90,000 g / mol, 95,000 g / mol, 100,000 g / mol, 105,000 g / mol, 110,000 g / mol, 115,000 g / mol, and 120,000 g / mol. Selecting a hydrogenated styrene-butadiene-styrene block copolymer with a weight-average molecular weight within the above range is beneficial for improving the plasticizing properties of the thermoplastic elastomer, thereby facilitating the formation of a smooth suction cup surface. Synergistically acting with other components of this application, it balances good adhesion and hardness, further enhancing the adsorption force between the suction cup and the adsorbed surface and extending the hanging time of the object.
[0033] In this application, hydrogenated styrene-butadiene-styrene block copolymers of different weight-average molecular weights can be purchased. For example, the hydrogenated styrene block copolymer in this application can be at least one of Kraton Regenerist G1654, TSRC 6153, and Lee Chang Yung Co. 7550.
[0034] In some embodiments, the mineral oil includes either naphthenic oil or paraffin oil.
[0035] In this application, mineral oils of different kinematic viscosities can be purchased. For example, the mineral oil in this application can be at least one of KN4010 and N4016 from Karamay Company.
[0036] In some embodiments, the softening point of poly(α-methylstyrene) is between 130°C and 150°C. Specifically, the softening point of poly(α-methylstyrene) may be, but is not limited to, 130°C, 132°C, 136°C, 140°C, 144°C, 148°C, and 150°C. A softening point within the above range can reduce its decomposition during the preparation of thermoplastic elastomers. Synergistically, with other components of this application, it helps the thermoplastic elastomer to better balance suitable viscosity and hardness, thereby further enhancing the adhesion between the suction cup and the adsorbed surface and extending the hanging time of the object.
[0037] The poly-α-methylstyrene with different softening points in this application can be obtained by purchase.
[0038] In some embodiments, the tackifier includes one of C9 petroleum resin or C5 petroleum resin.
[0039] The tackifier in this application can be purchased. For example, the tackifier in this application can be at least one of Ganges Petrochemical's C5 petroleum resin H5-1000 and C9 petroleum resin HM-1000.
[0040] In some embodiments, the raw materials further include antioxidants, including at least one of tris[2,4-di-tert-butylphenyl]phosphite and octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; based on the mass of the raw materials excluding the antioxidant, the antioxidant is present in parts by mass from 0.1 to 0.5 parts. Specifically, the antioxidant may be, but is not limited to, 0.1, 0.14, 0.18, 0.22, 0.26, 0.3, 0.34, 0.38, 0.42, 0.46, or 0.5 parts by mass. Adding the antioxidants in the above-mentioned parts by mass not only alleviates thermal aging of the material during processing and reduces the probability of polymerization degradation, but also helps to delay the thermal oxidative degradation of thermoplastic elastomers in air, improves the material stability of thermoplastic elastomers, and, when combined with the above components, allows the manufactured suction cups to maintain good adhesion and suspension performance while improving storage stability and extending service life.
[0041] The antioxidants used in this application are available for purchase.
[0042] The second aspect of this application provides a method for preparing a thermoplastic elastomer, comprising the following steps: mixing 25 to 40 parts by weight of hydrogenated styrene-butadiene-styrene block copolymer with 25 to 40 parts by weight of mineral oil to obtain a premix; mixing the premix with 2 to 7 parts by weight of polyα-methylstyrene and 15 to 35 parts by weight of a tackifier to obtain a mixture; and extruding and granulating the mixture to obtain a thermoplastic elastomer. By first mixing the styrene-butadiene-styrene block copolymer with mineral oil, the interaction between SEBS and mineral oil can be promoted, improving the dispersibility of each component, thereby improving the uniformity of the thermoplastic elastomer, reducing the probability of pitting, and obtaining a suction cup with a smooth surface, which is beneficial for improving the suction force and suspension performance of the suction cup.
[0043] In some embodiments, the premix is allowed to stand for 48 to 72 hours after the first mixing; specifically, the kinematic viscosity of the mineral oil can be, but is not limited to, 48, 52, 56, 60, 64, 68, or 72 hours. By controlling the first mixing time within the above range, it is beneficial to further promote the full interaction between SEBS and mineral oil, improve the uniformity of the thermoplastic elastomer, and thus obtain a suction cup with a good surface smoothness, thereby further improving the suction force and suspension performance of the suction cup.
[0044] This application does not impose any particular limitation on the temperature of the first mixture, as long as the purpose of this application can be achieved. For example, the temperature of the first mixture can be from 25°C to 55°C.
[0045] This application does not impose any particular limitation on the temperature of the second mixing step, as long as the purpose of this application is achieved. For example, the temperature of the second mixing step can be from 25°C to 55°C. This application does not impose any particular limitation on the time of the second mixing step, as long as the purpose of this application is achieved. For example, the time of the second mixing step can be from 0.5 hours to 2 hours.
[0046] In some embodiments, the extrusion temperature is between 170°C and 190°C. Specifically, the extrusion temperature can be, but is not limited to, 170°C, 172°C, 174°C, 176°C, 178°C, 180°C, 182°C, 184°C, 186°C, 188°C, and 190°C. By controlling the extrusion temperature within the above range, it is beneficial to achieve a molten homogenized state in the mixture and reduce the probability of molecular chain breakage, thereby reducing the risk of thermal degradation and thermo-oxidative aging of the mixture, resulting in a thermoplastic elastomer with good surface smoothness and few pits.
[0047] In some embodiments, the granulation process is water ring pelletizing, carried out in a solution containing an anti-sticking agent, which includes at least one of zinc stearate and calcium stearate. The thermoplastic elastomer of this application has good viscosity, making granulation difficult. By selecting the above-mentioned water ring pelletizing process and adding the above-mentioned anti-sticking agent to the solution, the processing performance of the thermoplastic elastomer is improved, the difficulty of granulation is reduced, and thermoplastic elastomer particles of suitable size and less prone to agglomeration are obtained. In subsequent processes, such as the feeding process of thermoplastic elastomer particles, this helps to reduce clogging and improve processing stability.
[0048] This application does not impose any particular limitation on the content of the anti-adhesive, as long as the purpose of this application is achieved. For example, based on the mass of water in the solution including the anti-adhesive, the mass percentage content of the anti-adhesive can be from 0.05% to 0.5%.
[0049] In some embodiments, the preparation method further includes the following steps: after extruding the mixture, it further includes passing the mixture sequentially through two layers of 300 mesh ± 10 mesh filters and two layers of 80 mesh ± 10 mesh filters. Specifically, the mesh size of the 300 mesh ± 10 mesh filters can be, but is not limited to, 290 mesh, 295 mesh, 300 mesh, 305 mesh, or 310 mesh; specifically, the mesh size of the 80 mesh ± 10 mesh filters can be, but is not limited to, 70 mesh, 75 mesh, 80 mesh, 85 mesh, or 90 mesh. This sieving process helps to further improve the gloss of the thermoplastic elastomer, reduce the number of pits, and thus reduce the defect rate of the thermoplastic elastomer particles. A third aspect of the present invention provides a suction cup, which includes the thermoplastic elastomer of any of the above embodiments or the thermoplastic elastomer prepared according to the method of any of the above embodiments. The suction cup provided by this application has a large adsorption force and good suspension performance.
[0050] This application does not impose any particular limitation on the method of preparing the suction cup. For example, the preparation process of the suction cup may include, but is not limited to, the following steps: preparing a base material such as a PC skeleton; then injecting a thermoplastic elastomer into a mold to wrap around a specific part of the PC skeleton, such as the edge of the PC skeleton; finally, coating the PC skeleton under a suitable injection temperature and pressure, so that the thermoplastic elastomer and PC form a mechanical interlock and / or chemical bond; and after cooling, opening the mold and removing the complete suction cup. This application does not impose any particular limitation on the above injection temperature, as long as the purpose of this application can be achieved. For example, the injection temperature can be from 180°C to 230°C. This application does not impose any particular limitation on the above pressure, for example, the above pressure can be from 20 bar to 100 bar.
[0051] The embodiments of this application will be described in detail below with reference to some examples. It should be understood that these embodiments are only for illustrating this application and are not intended to limit the scope of this application. For experimental methods in the following embodiments where conditions are not specified, please refer to the guidelines given in this application first, or follow experimental manuals or conventional conditions in the art, or follow the conditions recommended by the manufacturer, or refer to experimental methods known in the art.
[0052] In the following examples, the measurement parameters of the raw material components may have slight deviations within the weighing accuracy range unless otherwise specified. Temperature and time parameters are subject to acceptable deviations due to instrument testing accuracy or operational precision.
[0053] Test method:
[0054] Shore hardness test:
[0055] The Shore hardness of thermoplastic elastomers was tested according to the Shore A test method in ISO 868 / ASTM D2240.
[0056] Peel strength test:
[0057] Take the thermoplastic elastomers from each embodiment or comparative example, and coat them with a standard PC sheet (121.05mm ± 0.05mm in length, 40.16mm ± 0.05mm in width, and 2.36mm ± 0.02mm in thickness) on an injection molding machine at 200℃. Wrap the overmolding strip around the standard PC sheet to obtain the test sample. The above-mentioned test samples are as follows... Figure 1 and Figure 2As shown, the sample 01 to be tested includes a standard PC sheet 11 and an overlay strip 12 disposed on the surface of the standard PC sheet 11. The overlay strip 12 includes a clamping area 121, a transition area 122, and a covering area 123. The transition area 122 is located between the clamping area 121 and the covering area 123. The covering area 123 covers part of the surface of the standard PC sheet 11. The dimensions of the overlay strip are as follows: the length L1 of the clamping area is 30.34mm ± 0.05mm, and the width D1 of the clamping area is 20mm ± 0.05mm; the length L2 of the transition area is 30.21mm ± 0.05mm; the length L3 of the covering area is 119.91mm ± 0.05mm, and the width D2 of the covering area is 9.61mm ± 0.05mm; the thickness of the overlay strip is 2.24mm ± 0.02mm.
[0058] Place the standard PC sheet face down to fix the test sample on the peel strength standard test platform at the lower end of the universal testing machine (CMT6104). Clamp the holding area of the rubber strip in the test sample onto the upper clamp. Set the testing machine to stretch vertically upward at a constant speed of 50 mm / min until the PC sheet peels off from the rubber strip, and record the peel strength.
[0059] This application uses peel strength to evaluate the coating effect of thermoplastic elastomer on PC. The greater the peel strength, the better the coating effect; conversely, the smaller the peel strength, the worse the coating effect.
[0060] Suspension test:
[0061] The suction cups of each embodiment or comparative example were attached to tempered glass, and a 5KG weight was suspended on the suction cup. The test period was 15 days. Ten suction cups from each embodiment or each embodiment were tested. If more than nine of the weights did not fall off, it was considered excellent; otherwise, it was considered that the weights fell off.
[0062] Example 1:
[0063] The preparation steps of the thermoplastic elastomer in this embodiment are as follows:
[0064] (1) At 25°C, 25 parts by mass of hydrogenated styrene-butadiene-styrene block copolymer (7550 from Lee Chang Yung Co., Ltd., Taiwan) and 38 parts by mass of mineral oil (naphthenic oil, N 4016 from Karamay Co., Ltd.) were mixed to obtain a premix, and the premix was allowed to stand for 48 hours. The weight-average molecular weight of the hydrogenated styrene-butadiene-styrene block copolymer was 90,000 g / mol to 120,000 g / mol, and the kinematic viscosity of the mineral oil was 440 mm² / s.
[0065] (2) The premixed material after standing is mixed with 30 parts of tackifier (Henghe Petrochemical's C9 petroleum resin HM-1000), 7 parts of polyα-methylstyrene (Eastman 5140), and based on the mass of the above components, 0.1 parts of tris(2,4-di-tert-butylphenyl) phosphite (antioxidant 168) and 0.05 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol ester (antioxidant 1076) to obtain a mixture; wherein the softening point of the tackifier is 140℃.
[0066] (3) The mixture obtained in step (2) is extruded and water ring pelletized to obtain a thermoplastic elastomer; wherein the extrusion temperature is 180°C; after extrusion, it is passed through two layers of 300 mesh and two layers of 80 mesh filters at the extruder die head; in the solution used for water ring pelletizing, the mass percentage of calcium stearate anti-sticking agent is 0.1% based on the mass of water in the solution.
[0067] Finally, the suction cup is prepared: the thermoplastic elastomer obtained in step (3) is injected into the mold and wrapped around the edge of the PC skeleton (diameter of 52.5 mm, depth of 6.5 mm, thickness of 0.95 mm); finally, the PC skeleton is wrapped at an injection temperature of 190°C and a pressure of 35 bar, so that the thermoplastic elastomer and PC form mechanical interlock and chemical bonding. After cooling, the mold is opened and the complete suction cup is taken out.
[0068] The suction cup has the following dimensions: diameter 54mm, depth 8mm, and thickness 5mm.
[0069] Examples 2 to 6:
[0070] The preparation methods of the suction cups in Examples 2 to 6 are basically the same as those in Example 1, except that the relevant preparation parameters are adjusted according to Table 1.
[0071] Comparative Example 1:
[0072] The preparation method of the suction cup in Comparative Example 1 is the same as that in Example 1, except that the mineral oil is replaced with Karamay 100# mineral oil (paraffin oil) with a kinematic viscosity of 102.6 mm² / s.
[0073] Comparative Examples 2 to 4:
[0074] The preparation methods of the suction cups in Comparative Examples 2 to 4 are basically the same as those in Example 1, except that the relevant preparation parameters are adjusted according to Table 1.
[0075] Table 1
[0076]
[0077] In Table 1, " / " indicates that no relevant test parameters exist.
[0078] As can be seen from Examples 1 to 6 and Comparative Examples 1 to 4, the types and mass fractions of each component in the raw materials and the kinematic viscosity of the mineral oil in the examples are all within the range of this application. The resulting thermoplastic elastomer has a suitable Shore hardness, and the resulting suction cup has high peel strength, good adhesion, and good suspension performance. However, the kinematic viscosity of the mineral oil in Comparative Example 1 is too low. The thermoplastic elastomer raw material in Comparative Example 2 does not include poly-α-methylstyrene. Although the suction cups obtained in Comparative Examples 1 and 2 have high peel strength and good adhesion, they cannot pass the suspension test. In Comparative Example 3, the mass fraction of the mineral oil is higher than the range of this application and does not include a tackifier. The resulting suction cup not only has low peel strength and poor adhesion, but also cannot pass the suspension test. In Comparative Example 4, the content of the tackifier is too high. Although the resulting suction cup has high peel strength and good viscosity, it cannot pass the suspension test due to severe deformation during the injection molding process. This shows that the thermoplastic elastomer that meets the raw material composition requirements of this application has both good viscosity and hardness, so that the resulting suction cup can have good suspension performance while maintaining high adsorption force.
[0079] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0080] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A thermoplastic elastomer, characterized in that, The raw materials for preparing the thermoplastic elastomer, by weight, include the following components: 25 to 40 parts of hydrogenated styrene-butadiene-styrene block copolymer, 25 to 40 parts of mineral oil, 2 to 7 parts of polyα-methylstyrene, and 15 to 35 parts of tackifier. The kinematic viscosity of the mineral oil at 40°C is 420 mm² / s to 460 mm² / s.
2. The thermoplastic elastomer according to claim 1, characterized in that, The hydrogenated styrene-butadiene-styrene block copolymer has a linear structure and a weight-average molecular weight of 90,000 g / mol to 120,000 g / mol.
3. The thermoplastic elastomer according to claim 1, characterized in that, The mineral oil includes either naphthenic oil or paraffin oil.
4. The thermoplastic elastomer according to claim 1, characterized in that, The softening point of the poly-α-methylstyrene is 130°C to 150°C.
5. The thermoplastic elastomer according to claim 1, characterized in that, The tackifier includes either C9 petroleum resin or C5 petroleum resin.
6. The thermoplastic elastomer according to any one of claims 1 to 5, characterized in that, The raw materials also include antioxidants, which include at least one of tris[2,4-di-tert-butylphenyl]phosphite and β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester; Based on the mass of the raw materials excluding the antioxidant, the antioxidant is in the range of 0.1 to 0.5 parts by mass.
7. A method for preparing a thermoplastic elastomer, characterized in that, Includes the following steps: Based on parts by weight, 25 to 40 parts of hydrogenated styrene-butadiene-styrene block copolymer and 25 to 40 parts of mineral oil are first mixed to obtain a premix; The premix is then mixed a second time with 2 to 7 parts of poly-α-methylstyrene and 15 to 35 parts of a tackifier to obtain a mixture; The mixture is extruded and granulated to obtain the thermoplastic elastomer.
8. The preparation method according to claim 7, characterized in that, The preparation method satisfies at least one of the following characteristics: (1) After the first mixing, the premix is allowed to stand for 48 h to 72 h; (2) The extrusion temperature is 170°C to 190°C; (3) The granulation process is water ring granulation, which is carried out in a solution containing an anti-sticking agent, wherein the anti-sticking agent includes at least one of zinc stearate and calcium stearate.
9. The preparation method according to claim 7 or 8, characterized in that, After the mixture is extruded, the process further includes passing the mixture sequentially through two layers of 300 mesh ± 10 mesh filters and two layers of 80 mesh ± 10 mesh filters.
10. A suction cup, characterized in that, The suction cup comprises the thermoplastic elastomer according to any one of claims 1 to 6 or the thermoplastic elastomer prepared according to the preparation method according to any one of claims 7 to 9.